Evaluation of Knowledge, Attitude, and Practice of Parents on the use of Antibiotics for Acute Upper Respiratory Tract Infections in Children Admitted to Motahari Hospital of Urmia in 2017–2018 - Sadeghi, Ebrahim (Asian Journal of Pharmaceutics (AJP), 2018)
Background and Objective: As majority of upper respiratory tract infections (URTIs) have a viral origin, antibiotic prescription for URTIs has become a common practice in pediatric medicine. The prescription of an inappropriate and unnecessary antibiotic is the main cause of the development and increase of antibiotic resistance. The factors involved in high level of using antibiotics include knowledge and attitude on the use of antibiotics, patient satisfaction with treatment, and the relationship between physician and patient, and patient experience in the use of antibiotics. Thus, the objective of this research was to evaluate the knowledge, attitude, and practice (KAP) of parents with regard to the use of antibiotics for URTIs in children admitted to Infectious Diseases Clinic of Shahid Motahari Hospital in Urmia in 2017–2018. Methodology: The current research is an analytical cross-sectional study. The research population included parents who have children aged 1–8 years and admitted to the infectious diseases clinic of the Motahari Hospital in Urmia from all parts of the province. In this research, KAP of patients was evaluated with regard to the use of antibiotics for acute URTIs in children based on age, education level, and living place. SPSS software version 21 was used to analyze the data. Results: Of 400 parents examined, 58.8% were female and 41.2% were male. In addition, 75% of the parents were living in cities, 23.3% of them had academic level of education, and 12% were illiterate. A significant relationship was found between the level of education, the living place, and the KAP of parents with regard to the use of antibiotics for URTIs. There was also a significant relationship between age and attitude and practice of parents, but age was not significantly correlated with parent knowledge. Parents admitted to the hospital stated that the most reason for the arbitrarily use of antibiotics was its prescription by physician in the same condition. During 3 months before admitting to the hospital, 54.2% of the parents used the antibiotic arbitrarily for URTIs children. Conclusion: Low level of knowledge and attitude of parents about URTIs and high levels of arbitrarily use of antibiotic in this study make it necessary to provide educational programs for parents with regard to infections common among the children and, their treatment more supervision over pharmacies and retraining courses for physicians.